Analisis Dampak Regulasi Importasi Hasil Perikanan (2017-2023) Dalam Perspektif Hukum Investasi - Prayudi Budi Utomo; Binoto Nadapdap; Wiwik Sri Widiarty (Syntax Idea)
Investment regulations in Indonesia play a crucial role in enhancing business opportunities and investments. However, there exists an issue of overlapping regulations and implementation permits in the field that need to be addressed for greater effectiveness. Besides regulations, bureaucratic management also requires attention to improve investments due to its current lack of efficiency. The enhancement of investment regulations, capital injection, and improved implementation efficiency will significantly contribute to increased investments and business prospects in Indonesia. The primary issue in managing fisheries resources in Indonesia involves economic policies promoting the exploitation of fisheries resources and a lack of a robust management and law enforcement system. Central and regional government systems, work programs, and organizations need adjustments to support sustainable development in the fisheries sector. Through normative juridical research, primary legal data, theories, concepts, legal principles, and relevant legislation are studied. Policy reforms, regulatory system strengthening, import simplification, and infrastructure investments can improve the business environment. Consultations and discussions among the government, industry, and other stakeholders can align necessary regulations and ease business processes. The formation of regulations through the harmonization of investment-related rules in fisheries should adhere to investment law principles to create an appealing business environment for investors. The Indonesian government should also establish regulations supporting investments in the fisheries sector to achieve resource sustainability and economic growth.